Enhancement of shoot organogenesis in Polygonum tinctorium by sucrose and gelling agents - Park, Sang Un; Kil, Ki Jung (Journal of Phytology, 2022)
Indigo (Polygonum tinctorium), though it is a medicinal and dye crop, can also be grown in temperate areas, especially because it is commonly disseminated in Japan. To date, much research has been considered under investigation, especially for the regeneration of the indigo plant. Here in this study, we investigated the response of sucroses and gelling agents on the shoot organogenesis of the indigo plant. Micropropagation in terms of shoot regeneration and its growth was highly responded to sucrose and gelling agents. While culturing of internode explants on initial shoot regeneration media supplemented with sucrose and gelling agents of phytagar and gelrite significantly upgraded the regeneration efficiency as well as shoot growth. The regeneration capacity of the shoot was augmented with increased levels of sucrose up to 40 g L-1 and then started to decrease, whereas the increasing pattern continued even at the highest concentration (50 g L-1). The highest shoot regeneration (6.0 ± 0.5) was achieved by the treatment of 40 g L-1 giving 7.5 times higher shoot regeneration compared to the control. The increasing pattern for shoot length was more pronounced than that of shoot regeneration. The shoot length ranged from 10.2 mm to 23.5 mm within the sucrose treatments. In this study, the highest shoot length (23.5± 0.21) was observed by the treatment of 50 g L-1 exhibiting 2.3 times higher shoot length compared to the control. Gelling agent gelrite performed better than phytagar for both regeneration and shoot length growth. The shoot regeneration among the phytagar treatments ranged from 3.8 to 6.0 shoots/explant whereas the shoot regeneration ranged from 6.6 to 7.2 among the gelrite treatments. The highest shoots/explant (7.2) and the longest shoot length (22.4 mm) were observed due to the treatment of gelrite 3. The lowest shoot regeneration and shoot length were denoted when phytagar 9 was applied. It is proposed from our study that sucrose and gelling agent especially gelrite 3 could be applied in shoot organogenesis and plant transformation of any plant species, especially for P. tinctorium.